Appendicular fat mass is positively associated with femoral neck bone mineral density in older women - Elisa A Marques (2012)
Objective: In this study, we examined the relationships between body fat accumulation and distribution and bone mineral density (BMD) in older women. Methods: A total of 100 healthy white women (mean +/- SD age, 68.7 +/- 5.5 y) free of medications known to affect bone were enrolled. Lean mass, fat mass (FM), percentage body fat, android FM, gynoid FM, appendicular FM (AFM), appendicular lean mass, and femoral neck BMD were measured by dual-energy x-ray absorptiometry. Dietary intake was assessed by 4-day dietary record, and potential renal acid load was also calculated. Performance measures included knee extension and flexion strength measured on an isokinetic dynamometer. Physical activity was assessed using accelerometers and a questionnaire. Lactase nonpersistence was defined by the C/T-13910 genotype. Sociodemographic information, lifestyle behaviors, and clinical status were also examined. Stepwise multiple linear regression analysis showed that AFM was the most significant positive predictor of femoral neck BMD. Results: After adjustment for confounders (age, height, age at menopause, potential renal acid load, physical activity, and knee muscle strength), AFM had strong and independent associations with femoral neck BMD (26.4% of variance). Conclusions: These data highlight that in older women, localization of FM is more important for bone mass than obesity per se or lean mass. AFM (subcutaneous adiposity) seems to exhibit an independent protective effect on BMD.